Conserving an Endangered Canid: Assessing Distribution, Habitat Protection, and Connectivity for the Dhole (Cuon alpinus) in Bhutan - Thinley, Phuntsho; Rajaratnam, Rajanathan; Kamler, Jan F.; Wangmo, Cheten (Frontiers in Conservation Science, 2021)
Most canids face population declines and range contractions worldwide. Although the dhole (Cuon alpinus) is widely distributed across ten countries in South and Southeast Asia, limited studies exist on this species. Despite its globally ‘Endangered’ status and ecological role as an apex predator, assessments on its distribution are limited to a few landscapes and countries. This explains the lack of a dhole-specific species conservation plan in most range countries, including Bhutan where no current population estimate exists. The species has also recovered from a country-wide poisoning campaign in the 1970s and 80s. In this study, we determine the dhole’s distribution pattern and assess the protection and connectivity of dhole habitat in Bhutan. We anticipated dholes to be extant within their habitat well represented in protected areas (PAs) and biological corridors (BCs). We used 721 georeferenced dhole occurrence records and eight environmental variables in MaxEnt software to model potential dhole distribution and habitat suitability. The model output was overlaid on the spatial layers of PAs and BCs to assess habitat protection and connectivity. As anticipated, we found the dhole widely distributed in all districts, PAs, and BCs in Bhutan. Dholes were recorded at the highest elevation range limit of 4,980 m above sea level, which overlapped with the ‘Vulnerable’ snow leopard (Panthera uncia). Our model identified 72% (27,634 km2) of the country as suitable areas for dholes, of which, 31% (11,899 km2) was highly suitable and 41% (15,735 km2) was moderately suitable. Contrary to our expectation, PAs and BCs encompassed only 29% (8,046 km2) and 12% (3,185 km2) of suitable areas for dholes, respectively. A vast majority of the areas we deemed suitable for dholes currently remain unprotected, thus making dholes more vulnerable to human persecution and local extermination. We recommend adjusting PA boundaries to fully encompass suitable dhole habitat, and also advocate improved livestock husbandry to reduce dhole related livestock predation and minimize conflict, thereby ensuring its long-term survival in Bhutan.